An Integrated Analysis of LOTS–HOTS Distribution and Instructional Alignment in Indonesian Language Final Examination at SMP Negeri 2 Dayun - Agnessya Juliana; Alber (Jurnal PAJAR (Pendidikan dan Pengajaran), 2026)
This study aims to analyze the distribution of Lower Order Thinking Skills (LOTS) and Higher Order Thinking Skills (HOTS), as well as the alignment between test items and learning objectives in the odd-semester Final Examination (UAS) in the Indonesian Language subject at Grade VII at SMP Negeri 2 Dayun. This study employed a descriptive qualitative approach using content analysis of 50 examination items, answer keys, learning objectives, and interview data from the Indonesian Language teacher. The analysis was conducted based on the revised Bloom’s Taxonomy by Anderson, Krathwohl, and Webb’s alignment principles. The findings reveal that the examination is predominantly oriented toward LOTS, with 47 items (94%) categorized as LOTS and only 3 items (6%) classified as HOTS, mainly at the cognitive level C3 (applying). In addition, although 64% of the items were aligned with the learning objectives, 36% showed inconsistencies in cognitive demand, indicating that several test items did not adequately reflect the intended learning outcomes. This imbalance demonstrates that the assessment has not fully supported the development of students’ higher-order thinking skills, particularly critical, analytical, and creative thinking. The study highlights the need for more balanced and cognitively challenging assessment practices through the integration of HOTS-oriented items and stronger alignment between assessment instruments and instructional objectives. Scientifically, this study provides an evaluative framework for examining both cognitive level distribution and item alignment, which can serve as a reference for improving assessment quality in accordance with the principles of the Merdeka Curriculum.